1984
DOI: 10.1007/bf00427427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diazepam on plasma corticosterone levels

Abstract: In light of the numerous but rather conflicting reports on the action of benzodiazepines upon the hypothalamo-hypophyseal-adrenal (HHA) axis activity, the effect of different doses of diazepam (0.1, 1.0 and 10.0 mg/kg) administered 15, 30, 60, 120 and 240 min before decapitation on plasma corticosterone level was studied in rats. While 0.1 mg/kg diazepam had no effect, 1.0 mg/kg diazepam decreased plasma corticosterone levels 30 and 60 min following drug administration. On the other hand, treatment with 10.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
17
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 22 publications
6
17
0
Order By: Relevance
“…The reports showing the stimu latory effect of picrotoxin and bicuculline [10. 15, 17, 21], as well as the data showing the inhibitory effect of a low dose of diazepam (I mg/kg) on plasma corticosterone level [20,21] are in agreement with the hypothesis that GABA exerts an inhibitory effect on the HHA axis. Since we have shown that two pharmacological antagonists -picrotoxin, a GABA-A receptor blocker [see 3], and high doses of the GABA potentiating drug diazepam both elevate plasma Received: April 20, 1985 Accepted after revision: October 18, 1985 corticosterone level, we were interested in studying the mechanisms involved.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The reports showing the stimu latory effect of picrotoxin and bicuculline [10. 15, 17, 21], as well as the data showing the inhibitory effect of a low dose of diazepam (I mg/kg) on plasma corticosterone level [20,21] are in agreement with the hypothesis that GABA exerts an inhibitory effect on the HHA axis. Since we have shown that two pharmacological antagonists -picrotoxin, a GABA-A receptor blocker [see 3], and high doses of the GABA potentiating drug diazepam both elevate plasma Received: April 20, 1985 Accepted after revision: October 18, 1985 corticosterone level, we were interested in studying the mechanisms involved.…”
supporting
confidence: 75%
“…alters plasma corticosterone level in rats in two different ways [20). High doses of diazepam enhance [16,17,20], while low doses decrease plasma corticosterone levels in nonstressed rats [20,21]. The ability of a high dose of diaze pam to increase plasma corticosterone level in rats has also been reported by other authors [4,12,13,18].…”
mentioning
confidence: 54%
“…Similar nondrug-related stress effects are absent when CDP is administered via an intragastric cannula, indicating that this method of drug administration can be used successfully to study the actions of drugs on neuroendocrine parameters in undisturbed freely behaving rats. It has previously been shown that handling and intraperitoneal injection of saline results in an enhancement of plasma CS levels in rats (21,27). Furthermore, our CDP effects on plasma CS are in general agreement with several other studies (17,20,31) seen with the use of medium to high, sedative, doses of CDP and not with low doses, it has been suggested that these effects are related to the behaviorally depressant action of CDP (18,31).…”
Section: Methodssupporting
confidence: 92%
“…However, this appears not to be the case since anxiolytic doses of BDZs also elevate (dose-dependently) CS concentrations when administered acutely to unstressed rats (16,20,22,27,31). These anxiogenic or prostress effects are generally believed to arise from the sedative/ ataxic actions of BDZs (22,27,31), although such a relationship and Health Research MEDIGON (grant No. 900-548-087).…”
Section: Noradrenalinementioning
confidence: 99%
“…With this in mind, our research sought to further explore the effects of Nunavik R. rosea on the expression and extinction of fear memory using fear-potentiated startle (FPS), an animal model of anxiety-related behaviors (anxiolytic compounds decreases the FPS response in rodents; see Supporting Information for rodent information and FPS apparatus details; [11]). Additionally, some anxiolytics have significant effects on the release of stress-related glucocorticoid hormones [12,13]. Extracts of European populations of R. rosea inhibit stress-induced cortisol secretion [14,15], and plant adaptogens increase stress resistance and reduce the expression of stress-related biomarkers [16][17][18].…”
mentioning
confidence: 99%